2018
DOI: 10.1002/adfm.201804229
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Guided Engineering of Cytotoxic Cabazitaxel for an Adaptive Nanoparticle Formulation: Enhancing the Drug Safety and Therapeutic Efficacy

Abstract: Development of a sophisticated nanotherapeutic platform to deliver potent agents effectively and safely to desired tumor sites remains challenging. Cabazitaxel (CTX) holds particular interest for clinical use because of its ability to overcome the drug resistance caused by other taxane drugs. However, investigations of this potent agent have been met with only limited success due to its high toxicity in patients, and thus the exploration of CTX as a safe chemotherapeutic remains a tremendous challenge. Here, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 69 publications
1
31
1
Order By: Relevance
“…[4] The use of polymers as drug carriers aims to overcome these drawbacks through achieving longer circulation times, enhanced uptake in disease sites and increased specificity of delivery. [5][6][7] However, in order to obtain selective tumor uptake of nanoparticle drug carriers, the delivery systems must meet several criteria, such as an appropriate size range for diffusion out of the vasculature, prolonged circulation time in the bloodstream to allow for efficient uptake, reduced clearance from the bloodstream by avoidance of recognition by macrophages, and stability of the carrier during circulation. [8,9] Previous literature suggests that while larger nanocarriers have prolonged circulation times in the blood, particles over ≈100 nm suffer from poor tumor penetration, particularly in the case of poorly vascularized and necrotic/hypoxic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The use of polymers as drug carriers aims to overcome these drawbacks through achieving longer circulation times, enhanced uptake in disease sites and increased specificity of delivery. [5][6][7] However, in order to obtain selective tumor uptake of nanoparticle drug carriers, the delivery systems must meet several criteria, such as an appropriate size range for diffusion out of the vasculature, prolonged circulation time in the bloodstream to allow for efficient uptake, reduced clearance from the bloodstream by avoidance of recognition by macrophages, and stability of the carrier during circulation. [8,9] Previous literature suggests that while larger nanocarriers have prolonged circulation times in the blood, particles over ≈100 nm suffer from poor tumor penetration, particularly in the case of poorly vascularized and necrotic/hypoxic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used near-infrared (NIR) fluorescence imaging to assess the biodistribution of the nanotherapeutics in animals. This is a noninvasive technique with high sensitivity and enables real-time and quantitative analysis of NIR dye-labeled nanotherapeutics 31. Therefore, we covalently tethered the amine-bearing NIR dye Cy5.5 to the excess carboxyl group of the chitosan-CUR conjugates, yielding Cy5.5-labeled nCUR (termed Cy5.5-nCUR).…”
Section: Resultsmentioning
confidence: 99%
“…Jianqin et al found that chemical derivatization between oligolactide (oLA) and CTX provided better compatibility with the polymeric platform. With exogenous PEG–PLA, CTX and oLAs could form injectable nanomedicines, which displayed enhanced antitumor efficacy and amelioration of drug toxicity in a lung cancer xenograft model (Wan et al, 2018).…”
Section: Nanomedicine Delivery System For Overcoming Drug Resistancementioning
confidence: 99%